KESULITAN GURU MATA PELAJARAN AQIDAH AKHLAK DALAM MELAKUKAN PENILAIAN SIKAP PESERTA DIDIK PADA KELAS IV DI MADRASAH IBTIDAIYAH AT-TAQWA SAMBAS - Sri Alawiyah (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2016)
The purpose of this study is to reveal about: 1) How the Aqidah Akhlak subject teacher assesses student attitudes in grade IV at Madrasah Ibtidaiyah At-Taqwa Sambas for the 2019/2020 academic year; 2) The difficulty of the Aqidah Akhlak subject teacher in assessing the attitudes of students in grade IV at Madrasah Ibtidaiyah At-Taqwa Sambas for the 2019/2020 academic year. This study uses a qualitative approach and the type of descriptive research. Data collection techniques using interviews, observation and documentation. The data analysis techniques used are data reduction, data display and conclusions. The results of this study indicate that: 1. The difficulty of the Aqidah Akhlak subject teacher in assessing the attitudes of students in grade IV at Madrasah Ibtidaiyah At-Taqwa Sambas for the 2019/2020 academic year, namely the difficulty in determining attitude instruments in attitude assessment, lack of time to assess student attitudes, and difficulty developing attitude assessment criteria. 2. The method of Aqidah Akhlak subject teachers in assessing student attitudes in class IV at Madrasah Ibtidaiyah At-Taqwa Sambas for the 2019/2020 academic year consists of several ways, namely: 1) compiling the types of student attitudes; 2) observing students directly; 3) determine the attitude criteria according to the character of the students; and 4) increase cooperative relations.